SITE SPECIFIC RESPONSE SPECTRA ANALYSIS FOR SURALAYA REGION - (NIM 25006013), DELFEBRIYADI
Indonesia has been well known as one of the most seismically active countries in the world. Therefore, the building design in Indonesia should consider these seismic activities. Seismic hazard analysis for Suralaya region was developed based on SNI-1726-2002, that implements spectral hazard for 10 % probability of exceedance in building life time period of 50 years or corresponding to return period of approximately 475 years. The analyses were carried out using 2D earthquake source model and the seismic hazard analysis software named EZ-FRISK that is based on the total probability theorm. In this study, only seismic source zones within a radius of 500 km from the site are considered. Those outside this radius may not significantly influence the peak ground acceleration. There is no available strong motion data for Indonesia that is representative at this moment, therefore time history data for Suralaya site is generated synthetically by modifying the existing time history data using spectral matching analysis. The spectrum matching analysis was performed using SYNTH program. The actual ground motions from worldwide earthquakes were selected based on the similarity of their characteristics such as magnitude, distance and site conditions and then the spectrums were scaled for matching them with the spectrums from deaggregation analysis. Then, the ground response analyses were carried out using program NERA (Nonlinear Earthquake Response Analysis). The dynamic soil properties are obtained from the correlation with N-SPT and seismic downhole test from soil investigation report covering Suralaya site. The final result of this research are peak ground accelaration and the design response spectra on the Suralaya ground surface for 475 years return periods.